Rhodium-Catalyzed Cascade Annulative Coupling of 3,5-Diarylisoxazoles with Alkynes - Noguchi, Teppei; Nishii, Yuji; Miura, Masahiro (Synthesis, 2019)
A rhodium-catalyzed cascade annulative coupling of 3,5-diarylisoxazoles with three equivalents of an alkyne proceeds smoothly in the presence of a Cu(II) oxidant, where the sequential construction of isoquinoline and naphtho[1,8-bc]pyran frameworks connected by a biaryl linkage is achieved by a single operation. Most of the obtained polycyclic compounds exhibit visible fluorescence in both the solution and the solid state. The hexaphenylated isoquinoline-naphthopyran conjugate (R = Ph) as a representative product shows a green emission which can be turned off by making an isoquinolinium salt with an acid. The emission is also reversibly turned on by treatment with a base.
Keywords: C–H activation; annulative coupling; isoquinoline; rhodium catalyst; polyaromatic compounds